2022
DOI: 10.1037/edu0000649
|View full text |Cite
|
Sign up to set email alerts
|

Does triggering learners’ interest make them overconfident?

Abstract: Educators often use stories, humor, surprise, images, or other ploys to catch students' interest. This form of interest, often called "situational interest" because of how it is triggered by contextual cues, can facilitate learning to some degree. Yet it also may carry risks. This article proposes one such potential risk: flawed metacognition, in the form of inflated judgments of learning (JOLs) and overconfident estimates of future performance (calibration bias). Two experiments tested this hypothesis. In eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…The literature on learning with visualisations uses different terminologies when discussing interesting but irrelevant pictures. The different terms found in this field include seductive pictures (for recent studies, see e.g., Bender et al, 2021; Senko et al, 2022), decorative pictures (e.g., Lenzner et al, 2013; Schneider et al, 2018), and background images (Chung & Cheon, 2020). Regardless of the inconsistency in the terminology used, all the pictures in this category are aesthetically pleasing but unrelated to the instructional objectives, and are thus believed to distract students' attention (Sanchez & Wiley, 2006), and/or add extraneous load to students' limited working memory capacity (Mayer et al, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The literature on learning with visualisations uses different terminologies when discussing interesting but irrelevant pictures. The different terms found in this field include seductive pictures (for recent studies, see e.g., Bender et al, 2021; Senko et al, 2022), decorative pictures (e.g., Lenzner et al, 2013; Schneider et al, 2018), and background images (Chung & Cheon, 2020). Regardless of the inconsistency in the terminology used, all the pictures in this category are aesthetically pleasing but unrelated to the instructional objectives, and are thus believed to distract students' attention (Sanchez & Wiley, 2006), and/or add extraneous load to students' limited working memory capacity (Mayer et al, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The widely accepted notion of seductive detail effect assumes that interesting but tangential sources (e.g., funny images and interesting stories) can distract students from attending to key concepts, impeding their learning (Harp and Mayer, 1998; for a review, see Rey, 2012). More recently, Senko et al (2021) showed that interesting materials could also inflate students' judgment of learning and lead them to overestimate their performance. That is, more interesting materials can lead to a flawed conception of the student's mastery of the task.…”
Section: Joint Effects Of Competence and Interest On Negative Feedbac...mentioning
confidence: 99%